RESOURCE AND MARKET BASED DETERMINANTS OF PERFORMANCE IN THE U.S. BANKING INDUSTRY - Mehra, Ajay (Strategic Management Journal, 1996)
This paper explores the implications of studying industry competitive patterns at the level of resource accumulation and the relationship between resource endowments and firm performance outcomes in the U.S. banking industry. It uses the strategic group framework to evaluate two models of rivalry and performance and concludes by discussing the implications of the findings for competitive analysis, strategic group theory and the banking industry.